2014
DOI: 10.1080/09168451.2014.917260
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and genetic analyses of a carbazole-degrading gram-positive marine isolate, Janibacter sp. strain OC11

Abstract: Strain OC11 was isolated from seawater sampled at the coast of Chiba, Japan, in artificial seawater medium with carbazole (CAR) as the sole carbon source. Its 16S ribosomal RNA gene sequence suggested that strain OC11 belongs to the genus Janibacter. The CAR-degradation genes (car genes) of strain OC11 were PCR amplified, using degenerate primers designed based on the car gene sequences of other CAR-degrading bacteria. Complete nucleotide sequences encoding six complete open reading frames were determined, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…According to previous studies, the genus Janibacter showed broad metabolic versatility toward a variety of aromatic compounds such as fluorene, carbazole (Oba et al, 2014;Yamazoe et al, 2004), anthracene, phenanthrene, dibenzofuran (Jin et al, 2006), and polychlorinated biphenyls (Sierra et al, 2003).…”
Section: Relationship Between Microdiversity Of Marine Actinobacteria...mentioning
confidence: 99%
“…According to previous studies, the genus Janibacter showed broad metabolic versatility toward a variety of aromatic compounds such as fluorene, carbazole (Oba et al, 2014;Yamazoe et al, 2004), anthracene, phenanthrene, dibenzofuran (Jin et al, 2006), and polychlorinated biphenyls (Sierra et al, 2003).…”
Section: Relationship Between Microdiversity Of Marine Actinobacteria...mentioning
confidence: 99%
“…Two tertiary structures have been reported for type I extradiol dioxygenases: homo-octamer for BphC 3) and homotetramer for catechol 2,3-dioxygenase. 5) For heterooligomeric extradiol dioxygenase type II enzymes, α 2 β 2 heterotetramers were reported for protocatechuate 4,5-dioxygenase (LigAB), 6) 2′-aminobiphenyl-2,3-diol 1,2-dioxygenase (CarBaBb), [21][22] and 2-aminophenol 1,6-dioxygenase (CnbCaCb). 20) The results obtained from the gel filtration chromatography suggested that FlnD1D2 has an α 4 β 4 heterooctameric structure, indicating that this enzyme has a novel, functionally stable tertiary structure in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Janibacter sp. OC11 was later identified as the first marine Gram-positive carbazole degrader with a CARDO belonging to the class IIB like the one in strain IC177 (Oba et al 2014 ). Based on their diversity, known car gene clusters identified through heterologous expression and southern hybridization experiments were classified into three types: Pseudomonas -type ( car (P)), which shares homology with the car gene in P. resinovorans CA10; Sphingomonas -type car (SK), which shares homology with the car gene in Sphingomonas sp.…”
Section: Diversity Of Carbazole-degrading Bacteria Having the ...mentioning
confidence: 99%